IMPLEMENTASI PASAL 4 AYAT (2) PERATURAN DAERAH NOMOR 2 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN DI KOTA PEKANBARU TERHADAP LARANGAN MOBIL BARANG MENGANGKUT PENUMPANG - H.Silalahi, Syahron Fernando; Artina, Dessy; Rauf, Muhammad A. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
In article 137 of Law no. 22 of 2009 concerning Road Traffic andTransportation (UU LLAJ), it is regulated that goods cars are prohibited fromtransporting people. This refers to the definitions of goods cars and passengercars which are clearly different. So, drivers must be aware and careful not tocarry passengers. Every person who drives a goods car to transport people exceptfor the reasons as intended in Article 137 paragraph (4) letters a, b and c will bepunished with imprisonment for a maximum of 1 (one) month or a fine of amaximum of IDR 250,000.00 (two hundred fifty thousand rupiah)This type of research is empirical legal research, namely research usingfield data as the main data source, such as the results of interviews andobservations. Empirical research is used to analyze law which is seen aspatterned social behavior in people's lives which always interact and relate insocial aspects.From the results of the research and discussions carried out, several conclusionswere obtained, namely: First, Regional Regulation Number 2 of 2009 Article 4Paragraph (2) Concerning Road Traffic and Transportation in Pekanbaru Cityregarding the prohibition on goods cars carrying passengers in Pekanbaru hasbeen implemented since the regulation This issue has been published, but has notbeen implemented optimally by the traffic police because there are stilldiscretionary actions in the field. Second, factors inhibiting the traffic police fromenforcing regulations prohibiting goods cars from carrying passengers, namely,Public Awareness Factor, Lack of Capability of the Police, Cultural Factors,Page 2JOM Fakultas Hukum Universitas Riau Volume X Edisi 2 Juli – Desember 2023Health Factors. Third, the traffic police's efforts to tackle the use of goods carstransporting people in the city of Pekanbaru, namely, preventive efforts such asputting up banners on the roads prohibiting goods cars from transportingpassengers and carrying out patrols and raids at various points on public roads. ,repressive efforts such as education, fines with warnings, fines with confiscatedgoods. The author's advice is that it is necessary to implement these regulations inaccordance with the sanctions contained in regional regulations. If you still usediscretion in the field, you need to give a warning to drop off passengers andadvise you to board a passenger car for safety, and the public should have theawareness to always be orderly when passing traffic, don't make it happen. goodscar to transport passengers.Keywords: Prohibition, Traffic, Goods Cars Carrying Passengers